2018
DOI: 10.1101/415976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A seed resource for screening functionally redundant genes and isolation of new mutants impaired in CO2 and ABA responses

Abstract: The identification of homologous genes with functional overlap in forward genetic screens is $)! severely limited. Here we report the generation of over 14,000 amiRNA-expressing plants that $*! enable screens of the functionally redundant gene space in Arabidopsis. A protocol is developed %+! here for isolating robust and reproducible amiRNA-mutants. Examples of validation approaches %"! and essential controls are presented for two new amiRNA mutants that exhibit genetically %#! redundant phenotypes and circum… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 33 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Genomic DNA for candidate amiRNA lines was extracted (Kang, Cho, Yoon, & Eun, 1998) and used as templates, and the primers (primers pha2804f and pha3479r; Hauser et al, 2019); Table S1) were used to amplify the PCR product. The purified PCR samples were sent for sequencing to identify the amiRNA present (Hauser et al, 2019). The genes targeted by the amiRNA could be putatively identified by using the ‘Target Search Function’ on the WMD3 website (Ossowski, Fitz, Schwab, Riester, & Weigel, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Genomic DNA for candidate amiRNA lines was extracted (Kang, Cho, Yoon, & Eun, 1998) and used as templates, and the primers (primers pha2804f and pha3479r; Hauser et al, 2019); Table S1) were used to amplify the PCR product. The purified PCR samples were sent for sequencing to identify the amiRNA present (Hauser et al, 2019). The genes targeted by the amiRNA could be putatively identified by using the ‘Target Search Function’ on the WMD3 website (Ossowski, Fitz, Schwab, Riester, & Weigel, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The genes targeted by the amiRNA could be putatively identified by using the ‘Target Search Function’ on the WMD3 website (Ossowski, Fitz, Schwab, Riester, & Weigel, 2010). Several studies have demonstrated the accuracy of in‐silico predictions of amiRNA target genes (Hauser et al, 2013, 2019; Takahashi et al, 2020; Zhang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After stabilization of gs for 45–60 min, stomatal conductance of individual intact leaves was measured for 10 min in the dark, followed by red light (600 μmol m −2 s −1 ) exposure for 30 min. After red light treatment, blue light (10 μmol m −2 s −1 ) was applied and superimposed on red light, and stomatal conductance was measured for another 30 min as described previously (Shimazaki et al ., 2007; Hauser et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%